IMF Staff papers : Volume 34 No. 2. (IMF Staff Papers; IMF Staff Papers, 1987)
This paper studies the flow of primary commodity exports from non-oil exporting developing countries grouped by geographical region. The first part analyzes the changes in the structure of developing country commodity exports that have taken place over the past two decades. The second part presents empirical evidence on the response of commodity exports to demand and supply. These empirical results point to the low price and income elasticities of demand for certain primary commodity exports and to price elasticities of supply that are in general lower than the corresponding price elasticities of demand in the short run, but that are more sensitive to price in the longer run.